Salmonella Gallinarum virulence in experimentally-infected Japanese quails (Coturnix japonica) - Rocha-e-Silva,RC (2013)
Salmonella Gallinarum is the agent of fowl typhoid in poultry and infects mainly adult galliforms, causing significant economic losses in poultry production. Because quails are susceptible to this disease and quail production is becoming increasingly important in Brazil, this study was carried out to evaluate the virulence of Salmonella Gallinarum strain to quails. The inoculum was prepared from S. Gallinarum strain resistant to nalidixic acid. Forty eight 16-week-old Japanese quails were randomly distributed in three groups. Before the experiment, cloacal swabs were collected from all birds in order to confirm they were free from Salmonella spp. Cloacal swabs and fecal samples were collected on days 03, 06, 09, 12, and 15 post-inoculation. Birds that died during the experiment were submitted to post-mortem examination, and had their organs aseptically collected for bacteriological examination. All eggs produced during the experiment were also examined. The mortality rate recorded during the experiment was 43.75% (21/48). S. Gallinarum was recovered from the organs of the birds that naturally died during the experiment, but the agent was not isolated from the organs of sacrificed birds. No egg sample was positive for Salmonella Gallinarum. It was concluded that S. Gallinarum may be recovered from the organs of experimentally-infected Japanese quails.